Social work and the COVID-19 pandemic : international insights - Lavalette, Michael; Iakimidis Vasilios; Ferguson, Iain, 1954- (Policy Press, 2020)
As the world grapples with the complex impacts of COVID-19, this book provides an urgent critical exploration of how Social Work can and should respond to this global crisis. The book considers the ecological, epidemiological, ideological and political conditions which gave rise to the pandemic, before examining the ways that social work has responded in different nations across the Global North and Global South. This series of nation studies examine good practices and suggest new ways to renew and regenerate social work moving on from COVID-19. Contributors also reflect on the key themes that have emerged, including a rise in domestic violence and the ways that the pandemic has disproportionately affected those in working class and minority communities, exacerbating existing inequalities.